Sport and identity, or how to define ourselves - Caspistegui, Francisco Javier (Historia y Comunicación Social, 2012)
This article tries to show through various examples, the significance of sport in the shaping of human beings’ identities since the nineteenth century. The association with nationalism, totalitarian regimes and dictatorships, has not eroded the ability of sport to connect communities. In many cases, this inclusiveness has an important defensive feeling, preventing to consider sports practices as a mere reflection of modernity. Hence the need to historicize sporting identities, contextualizing and seeking interdisciplinary analysis to avoid reductionist views.